2022
DOI: 10.1101/2022.08.09.22278329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 convalescent plasma to treat hospitalised COVID-19 patients with or without underlying immunodeficiency: a randomized trial

Abstract: Background: Efficacy of COVID-19 convalescent plasma (CCP) in COVID-19 pneumonia is uncertain. Early transfusion of high antibody titre CCP may be beneficial, especially in case of underlying immunosuppression. Methods: The CORIPLASM study was a multicentric, open-label, Bayesian randomised clinical trial evaluating the efficacy of CCP in patients with moderate COVID-19 pneumonia, including patients with underlying immunosuppression. Patients hospitalised with COVID-19 for less than 9 days were assigned to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The literature search yielded 147 eligible studies, of which 9 controlled trials (4 randomized trials [20][21][22][23] and 5 cohort studies [24][25][26][27][28] ) were selected for meta-analysis, 13 uncontrolled large case series without individual patient data but totaling 358 patients were selected for descriptive analysis [29][30][31][32][33][34][35][36][37][38][39][40][41] , and 125 case reports/series totaling 265 patients met the eligibility criteria for individual patient data analysis, 35, . Reference 35 was included in both the descriptive analysis and the individual patient data analysis because individual patient data were available only for a subgroup of patients.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded 147 eligible studies, of which 9 controlled trials (4 randomized trials [20][21][22][23] and 5 cohort studies [24][25][26][27][28] ) were selected for meta-analysis, 13 uncontrolled large case series without individual patient data but totaling 358 patients were selected for descriptive analysis [29][30][31][32][33][34][35][36][37][38][39][40][41] , and 125 case reports/series totaling 265 patients met the eligibility criteria for individual patient data analysis, 35, . Reference 35 was included in both the descriptive analysis and the individual patient data analysis because individual patient data were available only for a subgroup of patients.…”
Section: Resultsmentioning
confidence: 99%
“…The process of study selection is represented in the PRISMA flow diagram (Figure 1). Three randomized clinical trials (RCTs) [28][29][30] enrolling 214 participants and 5 matched cohort studies [31][32][33][34][35] enrolling 1560 participants were included in the meta-analysis. Descriptive and exploratory analyses were performed on uncontrolled studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…In the primary meta-analysis of the 8 controlled trials (totaling 469 patients treated with COVID-19 convalescent plasma and 1305 controls), [28][29][30][31][32][33][34][35] the key findings are summarized in Table 3, Figure 2, and eFigure 1 in the Supplement. There was a high level of concordance among study outcomes, and treatment with COVID-19 convalescent plasma was associated with reduced risk of mortality according to the pooled risk ratio of 0.63 (95% CI, 0.50 to 0.79) and the pooled risk difference of −0.10 (95% CI, −0.15 to −0.06).…”
Section: Association Between Convalescent Plasma Transfusion and Mort...mentioning
confidence: 99%
“…49 Two further randomized trials which included a subgroup of immunosuppressed patients are available only as congress abstracts or preprints so far. 71,72 A total of 133 patients were included in the German RECOVER trial (NCT05200754), 71 patients with hematological malignancies, other cancers, or immunosuppression. Patients were randomized (1:1) to receive standard therapy alone or with CCP.…”
Section: Sars-cov-2 Antibody Concentration In Ccp Mattersmentioning
confidence: 99%
“…In contrast, the subgroup of 49 patients with hemato-oncologic disease showed a significant survival advantage for the CCP group (HR: 0.37; CI: 0.14-0.97). 72 An updated meta-analysis of CCP for the treatment of immunocompromised patients with COVID-19 by Senefeld and colleagues included 9 controlled studies (535 treated patients and 1,365 controls, including 4 randomized controlled trials), an individual patient data analysis of 125 case reports/series (265 patients), and a descriptive analysis of 13 uncontrolled large case series without individual patient data available (358 patients). The meta-analysis of controlled studies showed a mortality risk ratio of 0.65 comparing treatment with CCP versus standard of care for immunosuppressed COVID-19 patients.…”
Section: Sars-cov-2 Antibody Concentration In Ccp Mattersmentioning
confidence: 99%